Critical Assessment of Analytical Methods for the Harmonized and Cost-Efficient Analysis of Microplastics - Primpke, Sebastian; Christiansen, Silke H.; Cowger, Win; De Frond, Hannah; Deshpande, Ashok; Fischer, Marten; Holland, Erika B.; Meyns, Michaela; O'Donnell, Bridget A.; Oßmann, Barbara; Pittroff, Marco; Sarau, George; et al. (Applied Spectroscopy, 2020)
Microplastics are of major concerns for society and is currently in the focus of legislators and administrations. A small number of measures to reduce or remove primary sources of microplastics to the environment are currently coming into effect. At the moment, they have not yet tackled important topics such as food safety. However, recent developments such as the 2018 bill in California are requesting the analysis of microplastics in drinking water by standardized operational protocols. Administrations and analytical labs are facing an emerging field of methods for sampling, extraction, and analysis of microplastics, which complicate the establishment of standardized operational protocols. In this review, the state of the currently applied identification and quantification tools for microplastics are evaluated providing a harmonized guideline for future standardized operational protocols to cover these types of bills. The main focus is on the naked eye detection, general optical microscopy, the application of dye staining, flow cytometry, Fourier transform infrared spectroscopy (FT-Ir) and microscopy, Raman spectroscopy and microscopy, thermal degradation by pyrolysis–gas chromatography–mass spectrometry (py-GC-MS) as well as thermo-extraction and desorption gas chromatography–mass spectrometry (TED-GC-MS). Additional techniques are highlighted as well as the combined application of the analytical techniques suggested. An outlook is given on the emerging aspect of nanoplastic analysis. In all cases, the methods were screened for limitations, field work abilities and, if possible, estimated costs and summarized into a recommendation for a workflow covering the demands of society, legislation, and administration in cost efficient but still detailed manner.
CRIS-Team Scopus Importer:2020-10-02
Keywords: Fourier transform infrared spectroscopy; FT-IR; guideline; harmonization; microplastic; microscopy; nanoplastic; py-GC-MS; pyrolysis–gas chromatography–mass spectroscopy; Raman; Regulation; visually